5.9k views
0 votes
Please see picture for the question.

Please see picture for the question.-example-1
User Laurel
by
5.8k points

2 Answers

5 votes
When x, is 0, you just have to plug in 0 for x (and solve for y):

y = -2(0)+1

y = 1

So, your answer: y = 1
User Kbirk
by
6.8k points
5 votes
We have the following equation:
y = -2x + 1
For this case, the first thing to do is replace the value of x in the given equation.
So we have that for x = 0:
y = -2 (0) + 1
y = 0 + 1
y = 1
Therefore, the ordered pair solution is given by:
(x, y) = (0, 1)
Answer:
(x, y) = (0, 1)
x = 0
y = 1
User Satyaki
by
5.9k points